PENGARUH PENGUMUMAN PANDEMI COVID-19 DI INDONESIA TERHADAP HARGA SAHAM PERUSAHAAN LQ-45 DI BURSA EFEK INDONESIA - Suparmi Suparmi; I Putu Fery Karyada; Putu Nuniek Hutnaleontina (UNHI Press, 2022)
This study aims to determine the effect of the announcement of the Covid-19 pandemic in Indonesia on the stock price of LQ-45 on the Indonesia stoct Exchange. This type of research uses an event study. The population used is stock companies listed on the Indonesia Stock Exchange (IDX). The sampling method used purposive sampling, the research sample was 31 companies in LQ-45. This study uses a market model, the time used is 107 days. The data testing technique uses one sample t-test and paired sample t-test. The results of this study are that is no significant difference in the average abnormal return before and after the announcement of Covid-19 pandemic in Indonesia on the stock price of LQ-45 componies on the Indonesia Stock Exchange.